Adherens Junctions: Guardians of Cortical Development - Veeraval, Lenin; O’Leary, Conor J.; Cooper, Helen M. (Frontiers in Cell and Developmental Biology, 2020)
Apical radial glia (aRGs) comprise the pseudostratified neuroepithelium lining the embryonic lateral ventricles and give rise to the extensive repertoire of pyramidal neuronal subtypes of the neocortex. The establishment of a highly apicobasally polarized aRG morphology is a mandatory prerequisite for cortical development as it governs neurogenesis, neural migration and the integrity of the ventricular wall. As in all epithelia, cadherin-based adherens junctions (AJs) play an obligate role in the maintenance of aRG apicobasal polarity and neuroepithelial cohesion. In addition, the assembly of resilient AJs is critical to the integrity of the neuroepithelium which must resist the tensile forces arising from increasing CSF volume and other mechanical stresses associated with the expansion of the ventricles in the embryo and neonate. Junctional instability leads to the collapse of aRG morphology, disruption of the ventricular surface and cortical lamination defects due to failed neuronal migration. The fidelity of cortical development is therefore dependent on AJ assembly and stability. Mutations in genes known to control aRG junction formation are causative for a subset of inherited cortical malformations (neuronal heterotopias) as well as perinatal hydrocephalus, reinforcing the concept that aRG junctions are pivotal determinants of successful corticogenesis. In this review we explore the key animal studies that have revealed important insights into the role of AJs in maintaining aRG morphology and function, and as such, have provided a deeper understanding of the aberrant molecular and cellular processes contributing to debilitating cortical malformations. We highlight the reciprocal interactions between AJs and the epithelial polarity complexes that impose aRG apicobasal polarity. We also discuss the critical molecular networks promoting AJ assembly in aRGs and emphasize the role of the actin cytoskeleton in the stabilization of cadherin adhesion - a crucial factor in buffering the mechanical forces exerted as a consequence of cortical expansion.